KEDUDUKAN DAN HAK BANK TERHADAP HAK PREFEREN UPAH BURUH DALAM KEPAILITAN - Sukatra, I Wayan (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 6 No 3 (2017), 2018)
The Bank is the creditor holder of the right of security of material in the form of mortgage right, categorized as separatist creditor. Insurers' rights to land and other property related to the land, namely the right of Dependent, are the security rights imposed on the Land Rights referred to in UU no. 5 of 1960 on the UUPA. This separatist position can execute its right as if there was no bankruptcy". The right to sell on its own powers under Article 6 of the UUHT which is the embodiment of the right of the creditor's rights holder to the other creditor and does not require any further approval to the debtor to execute the guarantee goods. The Bank as a Separatist Creditor has a separate and irrevocable position and rights on the collateral pledged against it, whilst the preemptive right of wage workers with a pre-emptive right, when the enterprise is declared bankrupt or liquidated, wages and other rights of workers or workers constitute Debt which must be preceded by the payment, in Bankruptcy in Indonesia the position and the prefensity level is under separatist creditor. The notion of precedence here is not elaborated further and in detail that the wage bill must take precedence over any creditor, thereby leading to a legal confusion of both separatist creditors and other preferred creditors. Bank merupakan kreditor pemegang hak jaminan atas kebendaan berupa hak tanggungan,  masuk sebagai kreditor separatis. Tanah sebagai jaminan dan benda-benda yang berhubungan dengan tanah dapat dikatakan sebagai hak Tanggungan yaitu hak jaminan yang dijadikan beban atas kebendaan sesuai yang tercantum dalam Undang-Undang Pokok Agraria  ( UU No.5 Tahun 1960.) Kedudukan separatis ini bisa mengambil haknya seperti tidak ada putusan pailit.  Adapun hak tersebut  adalah hak untuk menjual sebagaimana benda tersebut hak miliknya sesuai ketentuan dalam Pasal 6 UUHT .merupakan perwujudan dari hak  kreditor separatis terhadap kreditor lainnya dan tidak memerlukan persetujuan lagi kepada debitor untuk melakukan eksekusi atas barang jaminannya. Bank sebagai Kreditor Separatis mempunyai kedudukan dan hak yang terpisah dan tidak dapat dikurangi atas barang jaminan yang diagunkan terhadapnya, sementara hak prefensi upah buruh yang memilki hak didahulukan, dan bila perusahaan dinyatakan pailit atau likuidasi, pembayaran tagihan/utang dan tagihan lainnya  dari pekerja   harus mendapatkan prioritas karena dalam Kepailitan di Indonesia kedudukan dan tingkat prefensinya adalah  di bawah kreditor separatis.